Peripheral and Central Vascular Access Devices: Dwell Time, Indications, and Complications (Narrative Review) - Drzewiecka, Antonina; Drzewiecki, Artur; Maciaszek, Oliwia; Mućka, Natalia; Grzela, Maciej (Quality in Sport, 2026)
Introduction and Purpose: Vascular access devices (VADs) are essential for modern inpatient care, yet optimal device selection remains complex due to heterogeneous data on dwell time, indications, and complications. Peripheral options such as midline catheters (MCs) and long peripheral catheters (LPCs) are increasingly proposed as alternatives to peripherally inserted central catheters (PICCs) and central venous catheters (CVCs), particularly for intermediate-duration therapy and in patients with difficult intravenous access (DIVA). The aim of this narrative review is to synthesize current evidence on peripheral and central vascular access, focusing on peripheral intravenous catheters (PIVCs), MCs, LPCs, PICCs, and CVCs, with respect to dwell time, therapeutic indications, and complication rates, including catheter-related bloodstream infections (CRBSI) and thrombosis. State of Knowledge: PIVCs, although most commonly used, have short dwell times and high failure rates, often complicated by phlebitis, infiltration, and occlusion. Midline catheters provide longer dwell times and reduce repeated cannulation but are associated with minor mechanical complications such as superficial thrombophlebitis and occlusion. PICCs and CVCs enable prolonged delivery of vesicant and hyperosmolar therapies but carry higher risks of bloodstream infection and venous thromboembolism. Comparative studies suggest midlines may reduce CRBSI and CLABSI-reportable events relative to PICCs, at the cost of more frequent minor complications. Conclusion: No single VAD is universally optimal. Device choice should integrate therapy duration, infusate characteristics, vascular anatomy, and the balance of infectious, thrombotic, and mechanical risks. MCs and LPCs appear promising for intermediate-duration, peripherally compatible therapies; however, high-quality randomized studies are needed to refine vascular access algorithms and confirm safety signals.